Reconstitution of the main demographic indices of the population exhumed from the mediaeval cemetery of Lozova (xivth-xvth centuries - Angela Simalcsik; Robert-Daniel Simalcsik; Vasilica -Monica Groza (Memoirs of the Scientific Sections of the Romanian Academy, 2013)
The scope of the present study was the demographic reconstitution of the population exhumed in the years 2010-2011 from the mediaeval cemetery of Lozova (Străşeni district, Republic of Moldova), belonging to the XIVth –XVth centuries. More than that, the demographic data obtained for the skeletal series of Lozova (51 skeletons) were compared with the data of other two synchronous mediaeval communities, namely with the human osteological material (32 skeletons) exhumed at Brăila – „Sf. Arhanghel Mihail” Church (XVth century) and with the human osteological material (101 skeletons) exhumed from the mediaeval cemetery of Hudum – Botoşani (XIIIth-XVth centuries). The population of Lozova is characterized by a high mortality of children and adolescents (39.2%). More than one third of the population did not attain the age of 20 years. The mortality ratio among adults attained 17.6%, while that of mature people – 43.1%. No survivor older than 60 years could be found. At the level of the whole population under analysis (0-x years), life expectancy at birth is of 27.23 years. For subjects older than 20, life expectancy is of 25.5 years – in both sexes. The average age of death calculated for the segment of adult population is of 36.5 years for men and of 42.0 years, respectively, for women, the values indicating a slight sexual dimorphism in favour of women (6 years more). The value of the masculinity index (22/13) indicates a higher ratio of men vs. women.